Incidence and regression of metabolic syndrome in a representative sample of the Spanish population: results of the cohort di@bet.es study. Issue 1 (13th October 2020) - Cuesta, Martín; Fuentes, Manuel; Rubio, Miguel; Bordiu, Elena; Barabash, Ana; Garcia de la Torre, Nuria; Rojo-Martinez, Gemma; Valdes, Sergio; Soriguer, Federico; Vendrell, Joan Josep; Urrutia, Ines Maria; Ortega, Emilio; et al.
Abstract : Introduction: Metabolic syndrome (MetS) is an important predictor of cardiovascular mortality. Identification of occurrence and regression trends of MetS could permit elaboration of preventive strategies with new targets. The objective of this study was to analyze the occurrence and regression rates of MetS and its associated factors in the representative cohort of Spain of the di@bet.es study. Research design and methods: The di@bet.es study is a prospective cohort where 5072 people representative of the Spanish population over 18 years of age were randomly selected between 2009 and 2010. Follow-up was a median of 7.5 (IQR 7.2–7.9) years, with 2408 (47%) participating subjects. A total of 1881 (78%) subjects had all the pertinent data available and were included in this study. Results: Of the 1146 subjects without baseline criteria for MetS, 294 (25.7%) developed MetS during follow-up, while of the 735 patients with prior MetS, 148 (20.1%) presented regression. Adjusted MetS incidence per 1000 person-years was 38 (95% CI 32 to 44), while regression incidence was 36 (95% CI 31 to 41). Regression rate was independently higher than incidence rate in the following: women, subjects aged 18–45, university-degree holders, patients without central obesity, without hypertension, as well as those with body mass index of <25 kg/m 2 . Lower progression and higher regression rates were observed with an adapted 14-point Mediterranean Diet adherence screener questionnaire score of >11 in both groups and with >500 and>2000 MET-min/week of physical activity, respectively. Conclusions: This study provides MetS incidence and regression rates, and identifies the target population for intervention strategies in Spain and possibly in other countries.